Correspondence between the ULF wave power spatial distribution and auroral oval boundaries - Kozyreva O.V.; Pilipenko V.A.; Engebretson M.J.; Klimushkin D.Yu.; Mager P.N. (Solar-Terrestrial Physics, 2016)
The world-wide spatial distribution of the wave power in the Pc5 band during magnetic storms has been compared with auroral oval boundaries. The poleward and equatorward auroral oval boundaries are estimated using either the British Antarctic Survey database containing IMAGE satellite UV observations of the aurora or the OVATION model based on the DMSP particle data. The “epicenter” of the spectral power of broadband Pc5 fluctuations during the storm growth phase is mapped inside the auroral oval. During the storm recovery phase, the spectral power of narrowband Pc5 waves, both in the dawn and dusk sectors, is mapped inside the auroral oval or around its equatorward boundary. This observational result confirms previously reported effects: the spatial/temporal variations of the Pc5 wave power in the morning/pre-noon sector are closely related to the dynamics of the auroral electrojet and magnetospheric field-aligned currents. At the same time, narrowband Pc5 waves demonstrate typical resonant features in the amplitude-phase latitudinal structure. Thus, the location of the auroral oval or its equatorward boundary is the preferred latitude for magnetospheric field-line Alfven resonator excitation. This effect is not taken into account by modern theories of ULF Pc5 waves, but it could be significant for the development of more adequate models.